Enhancing Vocabulary Acquisition in EFL Classes: The Effectiveness of Audio-Visual Aids - Ahmed, Toqeer; Shafi, Sehrish; Mahmood, Hifsa (Annals of Human and Social Sciences, 2024)
This research article investigates the effectiveness of audio-visual aids in enhancing vocabulary acquisition among secondary EFL (English as a Foreign Language) students. The study explores the impact of these aids on students' vocabulary learning compared to traditional teaching methods, aiming to determine whether multimedia resources can offer superior retention and engagement. The research includes a theoretical examination of vocabulary teaching strategies and a practical application of audio-visual aids in classroom settings. The methodology involves structured lesson plans, along with pre-test and post-test assessments to measure vocabulary retention. The study reveals that audio-visual aids significantly improve students’ vocabulary retention and engagement compared to conventional methods, supporting the integration of multimedia resources in EFL teaching for more dynamic and effective vocabulary instruction. This article provides insights and practical suggestions for EFL teachers to optimize their teaching practices using audio-visual tools, offering both theoretical and practical benefits for educators seeking to enhance their teaching strategies.